Research in Postgraduation: Is it an Area of Substantive Action to Improve at Universidad Nacional, Costa Rica? - Montero-Corrales, Carlos Alberto (2024)
Objective. The aim of this paper is to describe the distinguishing features of the postgraduate programs at Universidad Nacional (UNA), Costa Rica. This is done by characterizing the main research actions aimed at promoting academic research in science, technology, art, culture, and education in these programs. All these programs correspond to the Postgraduate Studies System at UNA (SEPUNA in Spanish). Method. This quantitative cross-sectional study examines information from a population of 1,400 students and 597 professors who participated in these programs between 2018 and 2020. The survey was used as a research technique; applying two questionnaires, one aimed at the student population with 698 responses and another at the teaching staff, with 194 responses in total. Results. The results show that the research conducted in the postgraduate programs requires the formulation and strengthening of research lines and research groups; both students and faculty are marginally dedicated to postgraduate studies, with a focus on teaching; professors participate significantly in the supervision of Final Graduation Projects; and it is identified by students and faculty that library services are the greatest stimulus that the college carries out in its postgraduate programs, but that the sense of self-efficacy of the student body needs to be strengthened within the postgraduate programs studied. Conclusions. The SEP and the Vice-Rectorate for Research must take action to create a scenario with more incentives and more time for research as a basis for the implementation of research lines and groups of postgraduate programs.